Coordinated expression of Borrelia burgdorferi complement regulator-acquiring surface proteins during the Lyme disease spirochete's mammal-tick infection cycle - Bykowski, Tomasz; Woodman, Michael E.; Cooley, Anne E.; Brissette, Catherine A.; Brade, Volker; Wallich, Reinhard; Kraiczy, Peter; Stevenson, Brian (Infection and immunity, 2007)
The Lyme disease spirochete, Borrelia burgdorferi, is largely resistant to being killed by its hosts' alternative complement activation pathway. One possible resistance mechanism of these bacteria is to coat their surfaces with host complement regulators, such as factor H. Five different B. burgdorferi outer surface proteins having affinities for factor H have been identified: complement regulator-acquiring surface protein 1 (BbCRASP-1), encoded by cspA; BbCRASP-2, encoded by cspZ; and three closely related proteins, BbCRASP-3, -4, and -5, encoded by erpP, erpC, and erpA, respectively. We now present analyses of the recently identified BbCRASP-2 and cspZ expression patterns throughout the B. burgdorferi infectious cycle, plus novel analyses of BbCRASP-1 and erp-encoded BbCRASPs. Our results, combined with data from earlier studies, indicate that BbCRASP-2 is produced primarily during established mammalian infection, while BbCRASP-1 is produced during tick-to-mammal and mammal-to-tick transmission stages but not during established mammalian infection, and Erp-BbCRASPs are produced from the time of transmission from infected ticks into mammals until they are later acquired by other feeding ticks. Transcription of cspZ and synthesis of BbCRASP-2 were severely repressed during cultivation in laboratory medium relative to mRNA levels observed during mammalian infection, and cspZ expression was influenced by culture temperature and pH, observations which will assist identification of the mechanisms employed by B. burgdorferi to control expression of this borrelial infection-associated protein.